PARTICIPATION IN STRATEGIC PLANNING: IMPLICATIONS FOR ACADEMIA - Saed Armia (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2011)
Well design of strategic planning is highly vital for higher education institution. This strategic planning becomes important foundation of how the universities/colleges leaders move their organization forward and on the track.  Therefore, one of important thing needed to be considered is engagement of important stake holders in formulation strategic planning such as lecturers, students, administration staffs are important groups that determine institution sustainability. To implement this process is not easy way out because each group has different interests that must be synergize to succeed strategic planning implementation. Although researches in this area are still limited, but one of important consideration we draw that it is important to have strong commitment support of top campus management to create an adaptive strategic plan. Keywords: Strategic planning, constituent engagement,       and academia